The Correlation of Family Support with Anxiety Level in Chronic Kidney Disease (CKD) Patient Undergoing Hemodialysis During the Covid-19 Pandemic - Pailungan, Ferly Yacoline; Kada, Maria Kurnyata Rante (Indonesian Journal of Global Health Research, 2025)
During the COVID-19 pandemic, major changes occurred in all aspects of life, requiring every individual to adapt to new situations and this led to various psychological problems, one of which was increased anxiety. This also has an impact on patients with chronic renal failure or chronic kidney disease (CKD) who have to undergo hemodialysis in the hospital, so to overcome anxiety, the role or support of the family is needed. This study was to determine the correlation between family support and anxiety in CKD patients undergoing hemodialysis during the COVID-19 pandemic. Design was correlation research with cross sectional design. The population is CKD patients undergoing hemodialysis at Bhayangkara Hospital and Labuang Baji Hospital Makassar, totaling 51 people. Sampling was done by consecutive sampling. The number of samples is 45 respondents. Data collection was carried out using a questionnaire which was an adaptation of the Zung Self-Rating Anxiety Scale instrument and a family support questionnaire developed by Nursalam. Validity and reliability tests were carried out on 30 respondents and obtained the results of the questionnaire r value on all statement items ranging from 0.397 - 0.924, (r count> r table) and Cronbach alpha value of 0.903, it was concluded that all statement items on the anxiety level questionnaire were valid and reliable to use. For the family support questionnaire, the r value on 20 statement items ranged from 0.619 - 0.927 with a Cronbach alpha of 0.961 so it was concluded that the questionnaire was valid and reliable to use. The data in this study were analysed using SPSS Version 22 software. Statistical tests using the Gamma correlation test showed a p value = 0.001 and an α = 0.05 (p < α) and a correlation value of 0.752. Based on the results of statistical tests, it can be concluded that there is a significant correlation between family support and anxiety in patients with chronic renal failure undergoing haemodialysis during the COVID-19 pandemic and shows a strong correlation.